Historical development of a scientific publication: Forty years of Latin American Journal of Psychology (2009)
The Latin American Journal of Psychology (RLP) was founded in 1969. In this article we present the historical context of psychology in Latin America when RLP was founded. An analysis of the main editorial characteristics is presented, including editorial board, peer review, financial aspects and distribution, structure, special volumes, types of articles published, authors' origin, and areas of psychology. The influence of RLP on the development of other journals in Latin America and Spain is examined. The role of RLP on the development of psychology in these regions is also discussed. It is argued that RLP has been one of the main editorial enterprises dedicated to the presentation of research production in psychology in Latin America, and has introduced several areas of psychology, unknown to the academic communities in the region.